Program Pelatihan dan Pendampingan Pemasaran Digital untuk Meningkatkan Kompetensi UMKM Bolsus Celebes di Makassar - Andi Balqis Mutiara Asizah; Valentino Aris; Muhammad Taufik; Andi Ruslan; Sri Asmirani (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
MSMEs are an important pillar of the Indonesian economy, yet many business actors still face limited digital literacy and unstructured marketing strategies. This condition was experienced by Bolsus Celebes MSME in Makassar, whose promotional activities were inconsistent and whose use of social media was not supported by structured content planning. This community service program aimed to improve the digital marketing competence of the owner and staff so they could implement more effective and sustainable promotional strategies through Instagram. Using a participatory action approach, the program was carried out through needs analysis, socialization, a one-day face-to-face training session, and three months of mentoring covering content planner development, content creation, and content publication. Evaluation was conducted through social media performance metrics and observation of the partner’s independence. The program produced 26 poster and reels contents and increased impressions by 5.1%, interactions by 17.8%, reach by 5.5%, profile visits by 41.2%, and followers by 28%. The results indicate that structured mentoring can improve the partner’s online visibility and independence in digital marketing.